Drought Analysis Using the Standardized Precipitation Evapotranspiration Index (SPEI) at Different Time Scales in an Arid Region - Raja, A.; Gopikrishnan, T. (Engineering, Technology & Applied Science Research, 2022)
Drought causes insufficient soil moisture and crop water balance damage. One of the most commonly used indicators in drought monitoring is the Standardized Precipitation Evapotranspiration Index (SPEI). In this study, the performance of the SPEI at 1-, 3-, 6-, 9-, and 12-month timescales was compared and analyzed from temporal and spatial variations at 12 meteorological stations in the Barmer arid region from 1979 to 2013. To determine the significance of drought characteristic trends, the modified Mann-Kendall (M-K) test is used. The results revealed that as the timescale increased, the temporal variations in the SPEI became more consistent. The M-K test revealed that the SPEI showed decreasing trends at 1 and 3 months, but increasing trends at 6, 9, and 12 months. The findings of this study are instructive and practical for drought assessment, risk management, and decision-making.